March of Time - Chaudhry, M. Lateef (Pakistan Journal of Ophthalmology, 2006)
Innovations in Cataract removal methods have been and are an ongoing process all along. Transitions from couching to intracapsular, extracapsular, IOL transplantation and somewhat recently to Phacoemulsification were undertaken with traditional anxiety and reluctance because of the realization that progress is inevitable and while remaining static would mean becoming decades behind the progressing world. As a matter of fact if one has not changed his surgical technique in the last three to four years he is already left behind one generation, likely to be labeled as outdated and under a serious threat of getting out of business. Once convinced of the benefits of Phacoemulsification and having crossed the hurdle of learning curve we soon became comfortable and confident with this technique passing on the benefits of Phacoemulsification to our patients who are now lot more happy, satisfied and unsacred of undergoing cataract surgery.